Slope deformation monitoring and early identification of disasters in debris flow source area of Baini River, Dongchuan District, China - Zhang, Xiaolun; Gan, Shu; Yuan, Xiping; Zong, Huilin; Wu, Xuequn (Frontiers in Earth Science, 2022)
Dongchuan District is one of the most densely distributed regions of geological disasters in the world. Geological disasters such as debris flows and landslides are serious threats to the lives and property safety of local people. Slope deformation monitoring and early identification of geological disasters in debris flow source areas are of great significance for disaster prevention and reduction. In this study, the time-series Synthetic Aperture Radar Interferometry (InSAR) technique was used to detect the deformation in the source area of the Baini river debris flow. The deformation rate in the middle part of the three-sided mountain is the largest, the average deformation rate is about 30 mm/year. The deformation rate of the lower and upper part of the mountain is slightly lower, but the deformation is creeping constantly, and obvious tensile cracks faced the river valley in the upper. The production and living areas of residents in 8 villages around the debris flow source area are constantly deformed, and there are different degrees of landslide risk. This study provides a scientific basis and reference for early identification, deformation analysis, disaster prevention and mitigation of geological disasters in the Xiaojiang Basin.